Keputusan Berlangganan Aplikasi Konferensi Video: Analisis Pengetahuan Konsumen dan Getok Tular Elektronik - Glorius Parulian Yuwono Setra; Rafika Puspitasari (President University, 2021)
The COVID-19 pandemic has minimized face-to-face meetings within the public. The reality shows that video-conference application is the solution so that people can still be connected face-to-face through online video even though they’re separated by distance and time. There are actually many video-conference applications on the market. However, Zoom Premium is considered to be popularly used and has become a public conversation since the COVID-19 pandemic. Someone who decides to subscribe to the Zoom Premium application is estimated to be influenced by their knowledge and public reviews that are scattered on social media regarding Zoom Premium. Therefore, this study aims to determine how much influence that product knowledge and electronic word-of-mouth (EWOM) have on the decision to subscribe to the Zoom Premium application. This study applies quantitative approach with online questionnaire being distributed through purposive sampling to one hundred and ten customers of the Zoom Premium application in Indonesia. The method used in this study is multiple regression analysis and utilizes the SPSS 25 application. The result shows that product knowledge and electronic word of mouth simultaneously influence 43.4% of the decision to subscribe to the Zoom Premium application. Partially, each of them is also influential.